PELAKSANAAN KEWENANGAN SATPOL PP DALAM PENEGAKKAN PERATURAN DAERAH NOMOR 27 TAHUN 1997 TENTANG KETERTIBAN UMUM STUDI DI KELURAHAN SUNGAI PAKNING KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Moris Adidi Yogia; Muhammad Nurzamani (UIR Press, 2015)
Social order is part of the ideals of the nation, with the situation of life in the community order would minimize social conflict. In connection with this study that raised an issue related to the social order. in the village of Bukit Batu subdistrict Kelurahan sungai pakning are social phenomena that could disrupt public order, livestock raising by way of removable without any safeguards, it received special attention and UPIKA district of government (District Leadership Element). Then out a policy in the form of circular regulating the control animals in District rocks. Policies that content rules and ban cattle raising by way of removable and no maintenance is at the spotlight in this skripsi research. Theory concept told by Ripley in book eran agus purwanto there are several indicators of research is, determine the policy goals and objectives, out policy, implementor, target group, the direct impact, medium impact, long term impact, implementing performance. By using research method quantitative and qualitative with observation technique and questionnaire question, interview by using informan key as information guest speaker and also through method of purposive sampling obtained from supplement informan. Result of this research is implementation of the civil service authority police force in the enforcement of local regulations numer 27 of 1997 on public order in the vilage studies sungai pakning districts rock bengkalis ,according to the lives stock owners are quite done well with the percentage of 50.58% and answers from the civil service police unit with a percentage of 71.11% performing well. And still there are inhibiting factors that affect the success of the policy that created, either of the factors that carry out policing (internal factors)as well as objects in the curb, and location of the area where the research problem ( external factors) and must be repaired and reviewed in order to create on orderly atmosphere in public life.